MODERASI BERAGAMA DALAM PENDIDIKAN DIASPORA: PRAKTIK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI COMMUNITY LEARNING CENTRE - Nova Tri Prasetiyo (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
This study addresses the growing urgency of religious moderation in responding to the complexity of intercultural interactions in the global era, particularly within diaspora education contexts. It aims to analyze teachers’ understanding, instructional practices, challenges, and strengthening strategies of religious moderation-based Islamic education in Community Learning Centre (CLC), Sabah, Malaysia. A qualitative case study approach was employed, involving four purposively selected teachers. Data were collected through Focus Group Discussions (FGDs) and field notes, and analyzed using thematic analysis. The findings reveal that religious moderation is understood not merely as a normative value but as a contextual social practice. Its implementation is adaptive, emphasizing dialogical, reflective, and experiential learning approaches, supported by the CLC environment as a social learning space. However, several challenges persist, including limited contextualized teaching materials, student heterogeneity, and insufficient systemic support. Accordingly, strengthening strategies should focus on developing adaptive and experience-based pedagogy. This study concludes that religious moderation functions as an essential social competence in fostering tolerance, adaptive capacity, and identity development among diaspora students.